2020
DOI: 10.7759/cureus.7561
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis as a Presentation of 2019 Novel Coronavirus Disease

Abstract: An emerging viral infection is a global public health challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
127
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 5 publications
3
127
1
4
Order By: Relevance
“…Subsequently two reports have emerged of rhabdomyolysis as either a presenting feature or a late complication of COVID-19. 58,59 One patient had limb pain and weakness with a peak CK of~12,000 U/L and myoglobulin >12,000 μg/L, and the other had a peak CK of 13,581 U/L. Neither patient had muscle biopsy performed.…”
Section: Other Covid-19 Related Neurological Disordersmentioning
confidence: 99%
“…Subsequently two reports have emerged of rhabdomyolysis as either a presenting feature or a late complication of COVID-19. 58,59 One patient had limb pain and weakness with a peak CK of~12,000 U/L and myoglobulin >12,000 μg/L, and the other had a peak CK of 13,581 U/L. Neither patient had muscle biopsy performed.…”
Section: Other Covid-19 Related Neurological Disordersmentioning
confidence: 99%
“… Day 12: negative COVID-19 nasopharyngeal swab. NR NR Admission: opinavir, moxifloxacin & interferon nebulization; Day 6: meropenem & methylprednisolone Day 9: IV fluid, plasma transfusion, IVIG & supportive care Favorable; recovery within few days ( Jin and Tong, 2020 ) New York, USA 88, M Acute progressive proximal lower limb weakness & myalgia Low-grade fever & tachypnea (on admission) ↑↑ CK (13,581 U/L), ↑ LDH (364 U/L), positive COVID-19 nasopharyngeal swab; AKI (day 7) NR NR IV fluid, hydroxychloroquine Favorable; ↓ CK within 6 days (368 U/L) ( Suwanwongse and Shabarek, 2020 ) New York, USA 75, F Four-day generalized weakness; evolving to lethargy, acute encephalopathy, & respiratory distress requiring ICU admission (day 3) Concurrent ↓ appetite Admission: ↑ CK (2767 U/L), ↑ troponin (0.663 ng/mL), normal EKG, hypernatremia (152 mM/L), AST (198 U/L), ALT (63 U/L), BUN (31 mg/dL) & creatinine (1.2 mg/dL); normal CBC diff . Day 2: positive COVID-19 nasopharyngeal swab, ↑ LDH (497 U/L), CRP (37 mg/L), D-dimer (573 μg/L) & ferritin (2134 μg/L) NR NR Day 2: azithromycin, hydroxychloroquine, vancomycin & cefepime.…”
Section: Neurologic Manifestationsmentioning
confidence: 99%
“…An early clinical study from Wuhan (Mao, Jin, 2020) reported that skeletal muscle injury, defined as myalgia plus hyperCKemia, were present in about 11% of patients with COVID-19. Although case reports of rhabdomyolysis with CK levels as high as >11,000 U/L have been reported in COVID-19 patients ( Table 2 ) ( Gefen et al, 2020 ; Jin and Tong, 2020 ; Suwanwongse and Shabarek, 2020 ), association of SARS-CoV-2 with either viral or necrotizing autoimmune myositis is still elusive. Two reported cases may indirectly suggest a SARS-CoV-2 triggered necrotizing autoimmune myositis ( Jin and Tong, 2020 , Suwanwongse and Shabarek, 2020 ).…”
Section: Neurologic Manifestationsmentioning
confidence: 99%
See 2 more Smart Citations